Contract farming, productivity and fertilizer usage: Empirical evidence from specialty crop production - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod Kumar; D'Souza, Alwin; Tripathi, Gaurav (International Food Policy Research Institute, 2018)
This study investigates the impact of contract farming (CF) in baby corn production on yield, irrigation costs, fertilizer costs and usage of chemical fertilizer. We find that adoption of CF by baby corn smallholders, after controlling for characteristics of both control and treatment groups, leads to higher yields and lower spending on fertilizers and irrigation. Additionally, CF in baby corn farming leads to a reduction in the use of chemical fertilizers (Urea and DAP). Thus, CF intervention benefits the livelihood of smallholders, reduces environmental degradation and reduces stress on groundwater without compromising yield.